Alice in Zombieland - Showalter, Gena. (Don Mills, Ont. : Harlequin, 2012)
Alice Bell must learn to fight the undead to avenge her family and learn to trust Cole Holland who has secrets of his own.
Series numbering from dust jkt.
Keywords: Zombies -- Juvenile fiction; Revenge -- Juvenile fiction; Orphans -- Juvenile fiction; Zombies -- Fiction; Revenge -- Fiction; Orphans -- Fiction; Young adult fiction